Perceptions of Erasmus students about European identity - Pehlivaner, Özlem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2006., 2006)
This study examines the European identity perceptions of Erasmus students. The nature of this study required a qualitative case study methodology using in-depth interviews to collect the data. This study attempted to answer the questions: What are perceptions of exchange students about European identity? Does participation in the Erasmus Program contribute to the creation of the European identity? The participants in this study were students who had applied to the European Commission to qualify for the Erasmus University Charter and also had scholarships as a result of the partnership between their own universities and Istanbul’s Boğaziçi University in 2005-2006 Fall. Ten participants were selected and interviewed during single meetings that were recorded. Full tape transcription was being used. The data were analyzed according to the inductive analysis approach. According to the findings, three definitions of “European” mainly emerged: one who is a citizen of the European Union, one who is from a country in Europe (from Moscow to Bosporus), and one who shares the history, culture and tradition of the European civilizations. According to findings, the Erasmus Program is a well known exchange program and accepted as an opportunity to provide different partnerships and grants. However, although the participants were affected by this exchange experience, only one emphasized that the program strengthened the European identity by bringing different students from different countries and different cultures together. It was not possible to say that the participants have a common European identity; however “being European” is an identifier for them.
Keywords: Student exchange programs -- Turkey.; Nationalism -- Europe.